Analisis Efisiensi Pelayanan Administrasi Pembayaran Terhadap Kepuasan Pelanggan Pada Perusahaan Listrik Negara Makassar - Mardiana Ibrahim; Bintang Balele (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of this research is to determine the influence of payment administration service efficiency factors on customer satisfaction at the State Electricity Company in Makassar, South Sulawesi Province. To find out which payment administration service efficiency variables have a more dominant influence on customer satisfaction at the State Electricity Company in Makassar, South Sulawesi Province. The research method used is a quantitative research method. Research results on the influence of Payment Administration service efficiency on customer satisfaction at the State Electricity Company in Makassar. In this research, results have been obtained that the hypothesis proposed is acceptable, because the results show that the efficiency of payment administration services has an effect on customer satisfaction at the State Electricity Company in Makassar. The research results also explain that the most dominant variable influencing customer satisfaction is the efficiency of payment administration service funds, where the results show that in general customers experience satisfaction because their expectations are the same as the implementation results (reality).